Feasibility study of a self-guided internet-based intervention for family caregivers of patients with cancer (OAse) - Grapp, Miriam; Ell, Johanna; Kiermeier, Senta; Haun, Markus W.; Kübler, Andrea; Friederich, Hans-Christoph; Maatouk, Imad (Scientific reports, 2022)
Despite high levels of distress, family caregivers of patients with cancer rarely seek psychosocial support and Internet-based interventions (IBIs) are a promising approach to reduce some access barriers. Therefore, we developed a self-guided IBI for family caregivers of patients with cancer (OAse), which, in addition to patients' spouses, also addresses other family members (e.g., adult children, parents). This study aimed to determine the feasibility of OAse (recruitment, dropout, adherence, participant satisfaction). Secondary outcomes were caregivers’ self-efficacy, emotional state, and supportive care needs. N = 41 family caregivers participated in the study (female: 65%), mostly spouses (71%), followed by children (20%), parents (7%), and friends (2%). Recruitment (47%), retention (68%), and adherence rates (76% completed at least 4 of 6 lessons) support the feasibility of OAse. Overall, the results showed a high degree of overall participant satisfaction (96%). There were no significant pre-post differences in secondary outcome criteria, but a trend toward improvement in managing difficult interactions/emotions (p = .06) and depression/anxiety (p = .06). Although the efficacy of the intervention remains to be investigated, our results suggest that OAse can be well implemented in caregivers’ daily lives and has the potential to improve family caregivers’ coping strategies.